The girl with the glass bird - Kerr, Esme (Chicken House/Scholastic Inc., 2015)
"At Knight's Haddon, a remote all-girls boarding school, feisty orphan Edie is assigned to spy on fragile, exotic Anastasia. Instead, the two become best friends--and discover a sinister mystery"--